Estimation of measurement uncertainty in an automated flowmeter calibration system - idrissa Deme (Brazilian Journal of Radiation Sciences)
The aim of this work is to estimate and analyze the measurement uncertainty in the calibration of liquid flow meters by the gravimetric method, which is a primary method. The calibration system used in this work is the calibration system for liquid flow meters of the National Institute of Metrology Quality and Technology -INMETRO that gives traceability to liquid flow meters in Brazil. The system that was fully operated manually went through an automation process in some of the components. The measurements were made in five ranges for a mass meter and the uncertainty expression followed the procedures of the Guide to the Expression of Uncertainty in Measurement (Iso-Gum). The results were compared with each other and  showed the performance of the meters according to the technology used in the measurement and the consistency of the calibration system.